2006
DOI: 10.1136/hrt.2004.050435
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the haemodynamics of different pacing sites in patients undergoing resynchronisation treatment: need for individualisation of lead localisation

Abstract: Individualisation of pacing configuration for biventricular pacing leads to further haemodynamic improvement in patients with heart failure and reduces the number of patients not responding to this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…This mechanism may in part explain the significant intraindividual and interindividual variability that has been found in other studies in the optimal LV lead position in patients undergoing CRT. 4,5 In our study, a lateral position of the LV endocardial lead was shown to be superior to posterior or anterior lead positions when pacing outside areas of slow conduction. This is consistent with the premise that resynchronization therapy is best delivered using a laterally positioned electrode to reverse the effect of LV dyssynchrony, which gives rise to late activation of the lateral LV wall.…”
Section: Variations In Hemodynamic Response To LV Pacingmentioning
confidence: 94%
See 1 more Smart Citation
“…This mechanism may in part explain the significant intraindividual and interindividual variability that has been found in other studies in the optimal LV lead position in patients undergoing CRT. 4,5 In our study, a lateral position of the LV endocardial lead was shown to be superior to posterior or anterior lead positions when pacing outside areas of slow conduction. This is consistent with the premise that resynchronization therapy is best delivered using a laterally positioned electrode to reverse the effect of LV dyssynchrony, which gives rise to late activation of the lateral LV wall.…”
Section: Variations In Hemodynamic Response To LV Pacingmentioning
confidence: 94%
“…In keeping with this concept, other investigators have demonstrated using acute hemodynamic studies that the optimal LV lead position varies considerably between patients and may need to be optimized on an individual basis. 4,5 However, a major limitation of the coronary sinus approach is the limited number of optimal sites available to capture.…”
Section: Clinical Perspective On P 179mentioning
confidence: 99%
“…5, 6 Many factors have been associated to a poor response, including pacing from areas of scar, 18 enrolling patients with only slightly enlarged QRS (<150 ms), 19 LV lead positioning in an anterior branch of the CS. 7 Recently, data from the MADIT-CRT trial suggested that the response to biventricular pacing may vary according to the site of pacing, with the midventricular and basal portions of the lateral wall generally associated with a better response compared with apical sites. 8 Although most of the available devices allow many configurations of LV pacing (tip to ring, ring to tip, tip to coil, etc), the pacing site remains substantially unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have concentrated on the position of the LV lead with respect to acute and chronic response to CRT [22,23,30,31]. The positioning of the RV lead in relation to CRT response is less well understood.…”
Section: Septal Vs Apical Rv Lead Positionmentioning
confidence: 99%
“…Acute response was defined as an improvement in LV dP/dt max of ≥10% versus fixed rate atrial/RV pacing [22,23]. Patients were deemed to have remodelled if at 6 months post implant there was a ≥15% reduction in LV end-systolic volume (ESV) measured using Simpson's modified biplane method on 2D echo images [24,25].…”
Section: Classification Of Acute and Chronic Responsementioning
confidence: 99%